Human Resource Management Practices In Life Insurance Corporation of India: Understanding the Role of Human Resource Management in Organizational Performance (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The terms ‘human resource management’ (HRM) and ‘humanresources’ (HR) have largely replaced the term ‘personnel management’ as adescription of the processes involved in managing people in organizations. Theconcept of HRM underpins all the activities to provide a framework for whatfollows by defining the concepts of HRM and an HR system, describing thevarious models of HRM and discussing its aims, characteristics, HRM and therelationship between HRM and personnel management and the impact HRM can makeon organizational performance.